Awareness of cervical cancer risk factors and screening methods among women attending a tertiary hospital in Lucknow, India - Nigar, Asma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the second most common cancers among women worldwide after breast cancer. It is the only cancer in which early diagnosis of precancerous lesions can be done by a very simple and sensitive test that is, paps test. Knowledge of the women about cervical cancer risk factors and awareness about its screening are the key factors that may decrease the mortality and morbidity caused by cancer cervix. Most of the cases of cervical cancer in India are diagnosed very late, because of lack of awareness about risk factors and screening methods, resulting in fatal outcome. So, this study was done to assess the knowledge of risk factors for cervical cancer, and paps smear test for its screening. Methods: This cross-sectional study was conducted among 200 women aged 18-55 years, attending Gynaecology Out-Patient Department (OPD) in a tertiary care hospital in Lucknow. Information about their knowledge of cervical cancer, awareness of its prevention and their socio demographic characters were collected by a questionnaire. Results: Majority (47%) of the females were in 26-35 years of age. (81.5%) were from rural background. 88% women were not aware of cervical cancer and its risk factors. 6.5% women were aware of the paps test. 8% were aware of probability of early diagnosis. Majority (98.5%) were not aware of vaccination as prevention for cervical cancer. Conclusions: Present study population shows very poor knowledge about cervical cancer risk factors and is unaware of the concept of prevention. Hence extensive health education to the public is needed regarding cervical cancer and its prevention.